CLINICAL AND HEAT RESISTANCE INDICATORS OF DAIRY COWS - Kholjigitov Askar Marifjonovich; Yangiboyev Abdimalik Eshmurodovich (Scholar Express Journal, 2023)
Cows use physiological indicators, characterizing internal organs, such as body temperature, frequency of heart rate and frequency of breathing, izuchameye kak optimal indicators for internal research, and physiological and biochemical processes, originating in the organism, yavlyayutsya factors, characterizing health status and ego effectiveness.
Keywords: Cow; blood; clinical; heat endurance